2014
DOI: 10.1186/1475-2867-14-19
|View full text |Cite
|
Sign up to set email alerts
|

Par6 is an essential mediator of apoptotic response to transforming growth factor beta in NMuMG immortalized mammary cells

Abstract: BackgroundWe previously observed that the TGFbeta-Par6 pathway mediates loss of polarity and apoptosis in NMuMG cells. Here we investigate the contribution of Par6 versus TGFbeta receptor I activation to TGFbeta-induced apoptosis in association with changes in apico-basal polarity. We focus on the effect of Par6 activation on alpha6beta4 integrin expression and localization, and Nuclear Factor-kappaB (p65/RelA) activation, previously shown to mediate polarity-dependent cell survival.MethodsUsing immunoblotting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
1
22
1
Order By: Relevance
“…We therefore determined the expression patterns of Par6 in the U87MG, U251, and HEB cell lines ( Figure 1D). 10,23,25,29,30 In addition, we found that Par6 expression was much higher in either U87MG or U251 cells than that in HEB cells. 10,23,25,29,30 In addition, we found that Par6 expression was much higher in either U87MG or U251 cells than that in HEB cells.…”
Section: Aberrant Expression Of Par6 In Glioma Tissues and Cellsmentioning
confidence: 66%
See 4 more Smart Citations
“…We therefore determined the expression patterns of Par6 in the U87MG, U251, and HEB cell lines ( Figure 1D). 10,23,25,29,30 In addition, we found that Par6 expression was much higher in either U87MG or U251 cells than that in HEB cells. 10,23,25,29,30 In addition, we found that Par6 expression was much higher in either U87MG or U251 cells than that in HEB cells.…”
Section: Aberrant Expression Of Par6 In Glioma Tissues and Cellsmentioning
confidence: 66%
“…Our immunostaining results indicated that Par6 localized in either the cytoplasm or cell membrane in the glioma cell lines U87MG and U251, inconsistent with the localization in epithelial tumor cells reported previously. 10,23,25,29,30 In addition, we found that Par6 expression was much higher in either U87MG or U251 cells than that in HEB cells. Thus, this different expression pattern of Par6 between glioma cells and human malignant epithelial tumor cells suggests that the functions of Par6 in glioma might be different than those in malignant epithelial tumors.…”
Section: Aberrant Expression Of Par6 In Glioma Tissues and Cellsmentioning
confidence: 66%
See 3 more Smart Citations